Implications of obesity for tendon structure, ultrastructure and biochemistry: A study on Zucker rats - Biancalana, Adriano; Velloso, Licio Augusto; Taboga, Sebastiao Roberto [UNESP]; Gomes, Laurecir (Pergamon-Elsevier B.V. Ltd, 2012)
The extracellular matrix consists of collagen, proteoglycans and non-collagen proteins. The incidence of obesity and associated diseases is currently increasing in developed countries. Obesity is considered to be a disease of modern times, and genes predisposing to the disease have been identified in humans and animals. The objective of the present study was to compare the morphological and biochemical aspects of the deep digital flexor tendon of lean (Fa/Fa or Fa/fa) and genetically obese (fa/fa) Zucker rats. Ultrastructural analysis showed the presence of lipid droplets in both groups, whereas disorganized collagen fibril bundles were observed in obese animals. Lean animals presented a larger amount of non-collagen proteins and glycosaminoglycans than obese rats. We propose that the overweight and lesser physical activity in obese animals may have provoked the alterations in the composition and organization of extracellular matrix components but a genetic mechanism cannot be excluded. These alterations might be related to organizational and structural modifications in the collagen bundles that influence the mechanical properties of tendons and the progression to a pathological state. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Zucker rats; Obesity; Tendon; Morphology; Glycosaminoglycans